2019
DOI: 10.4028/www.scientific.net/kem.811.40
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids in <i>Tamarindus indica</i> L. Seeds Oil and Antibacterial Activity Assay

Abstract: The research was conducted to investigate the oil and fatty acids contained in Tamarindus indica Linn (tamarind) seeds oil. Tamarind seeds oil was isolated by extraction and fractionation. The fatty acids content in oil were identified as fatty acid methyl ester. Fatty acid methyl ester was produced from trans-esterification reaction of tamarind seed oil with methanol and boron trifluoride catalyst (MeOH/BF3). Identification of fatty acid methyl ester was carried out by gas chromatograph mass spectrometry (GC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 16 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…In several countries on the African and Asian continents, it was reported that the fruit, leaves, and bark of the tamarind flowers are used in the pharmaceutical industry and traditional medicine as a laxative, antithrombotic, wound treatment, diarrhea, abdominal pain, dysentery, constipation, snake bites, colds, inflammation, helminth infection, and fever so that it can play a role as antimicrobial, antidiabetic, anti-inflammatory and effects on satiety control, potential in the treatment or prevention of obesity and other chronic diseases (Havinga et al, 2010;Krishna, Anitha, & Ezhilarasan, 2020;Kuru, 2014;Menezes, Trevisan, Barbalho, & Guiguer, 2016;Rizkiany, Amelia, Bimantara, Sagami, & Basyuni, 2021;Saputri, Avatara, & Rachmawati, 2018). In particular, the flower's concentration of extracts and seed oil can be used as antioxidants (Souza et al, 2020;Sutrisno, Retnosari, Marfu'ah, & Fajaroh, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In several countries on the African and Asian continents, it was reported that the fruit, leaves, and bark of the tamarind flowers are used in the pharmaceutical industry and traditional medicine as a laxative, antithrombotic, wound treatment, diarrhea, abdominal pain, dysentery, constipation, snake bites, colds, inflammation, helminth infection, and fever so that it can play a role as antimicrobial, antidiabetic, anti-inflammatory and effects on satiety control, potential in the treatment or prevention of obesity and other chronic diseases (Havinga et al, 2010;Krishna, Anitha, & Ezhilarasan, 2020;Kuru, 2014;Menezes, Trevisan, Barbalho, & Guiguer, 2016;Rizkiany, Amelia, Bimantara, Sagami, & Basyuni, 2021;Saputri, Avatara, & Rachmawati, 2018). In particular, the flower's concentration of extracts and seed oil can be used as antioxidants (Souza et al, 2020;Sutrisno, Retnosari, Marfu'ah, & Fajaroh, 2019).…”
Section: Introductionmentioning
confidence: 99%